71 The Use of Sternocleidomastoid Rotational and Cervicofacial Advancement Flap for Closure of a Persistent Mastoid Cutaneous Fistula. (12th October 2021) - Mantelakis, A; Tsitsiou, Y; Joshi, A
Abstract: Introduction: Postauricular mastoid fistula is a rare occurrence, typically following repeated soft tissue injury, commonly caused by chronic suppurative otitis media and repeated surgical treatments. Management is challenging with a limited number of reported, successful surgical techniques, which often have limited applicability. Case report: We present a case of a 55-year-old male patient with a persistent right post-auricular cutaneous mastoid fistula as a result of two previous mastoidectomies. Although the patient underwent two simple primary closures, the fistula recurred. This was successfully treated with a new technique utilising a Sternocleidomastoid Rotational and Cervicofascial Advancement Flap which was completely healed at the 1-year follow-up without a recurrence of the fistula. Conclusions: This novel technique provided a definitive obliteration of a persistent cutaneous mastoid fistula. By utilising a double layered flap, via a facelift incision, the flap results in an excellent functional and cosmetic result.